A literature review on the effects of 6-Dimensional virtual reality's sport applications toward higher presense - Mahalil I.; Yusof A.M.; Ibrahim N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Health; Virtual reality; Wind effects; Breathing masks; Feeling of presences; High-fidelity; Higher-dimensional; Human sense; Literature reviews; Sense of presences; VR applications; Sports